Baseline serum levels of multiple cytokines and adhesion molecules in patients with acute myeloid leukemia: results of a pivotal trial - Kupsa, T.; Vasatova, M.; Karesova, I.; Zak, P.; Horacek, J.M. (Experimental Oncology, 2014)
Aim: Evaluation of serum levels of 17 cytokines and 5 adhesion molecules in patients with newly diagnosed acute myeloid leukemia (AML) using biochip array technology. We searched for links between baseline levels and age, hyperleukocytosis, secondary origin of AML, resistance to induction therapy with cytarabine and daunorubicin and standard risk stratification according to cytogenetics and molecular genetics. Methods: We evaluated the sera of 51 consecutive patients. Serum samples were analyzed by biochip based immunoassays on the Evidence Investigator analyzer. T-tests were used for statistical analysis. Results: We found that higher age is associated with lower levels of interleukin (IL)-12. Patients with secondary disease were older, had higher levels of EGF and IL-7, and lower levels of E-selectin, IL-12 and IL-13. In hyperleukocytosis, the levels of IL-1β, IL-2, TNF-α, VCAM-1, ICAM-1, E-selectin and L-selectin were increased, whereas levels of IFN-γ and MCP-1 were decreased. In patients who failed to achieve complete remission after induction therapy, we found lower E-selectin and P-selectin levels. High risk patients had lower levels of IFN-γ. Conclusion: Some leukemic cell subpopulations have the ability to produce cytokines that modulate the microenvironment by inducing inflammation. This causes endothelial cells to be activated and overexpress adhesion molecules. Hyperleukocytosis and secondary origin of the disease are the major factors influencing the cytokine and adhesion molecule profile in newly diagnosed AML patients. Key Words: cytokines, adhesion molecules, biochip array, acute myeloid leukemia.